Manajemen Pendidikan - Syamsurijal Basri; Sri Hastuti; Fausiah (Irfani, 2025)
This study examines extracurricular management at SD Islam Al Azhar 34 Makassar. The focus of this study is: How is extracurricular management and the supporting and inhibiting factors that influence the success of Swimming and Dance extracurricular management at SD Islam Al Azhar 34 Makassar. The purpose of this study is to determine the management system for Swimming and Dance extracurricular activities at SD Islam Al Azhar 34 Makassar, including: planning, organizing, implementing, supervising and evaluating extracurricular activities as well as the supporting and inhibiting factors. This research approach is qualitative with a descriptive research type with research subjects including the Principal, Vice Principal for Student Affairs, and Extracurricular Supervisor. Data collection uses interviews, observation and documentation. The data obtained are analyzed through word reduction, data presentation, and conclusion drawing. The results of the study indicate that (1) Management of Extracurricular activities at SD Islam Al Azhar 34 Makassar in the Planning aspect is in accordance with Permendikbudristek No. 12 of 2024 concerning Curriculum in Early Childhood Education, Elementary Education Level, and Secondary Education Level which includes: activity planning procedures, activity curriculum, and strategies for compiling extracurricular activities. Organization is carried out through a clear structure, involving all responsible persons. The division of tasks and responsibilities is carried out periodically to facilitate coordination. Management of funds, schedules, and facilities is coordinated, and supported by competent supervisors. Implementation Includes: implementation methods, activity schedules, and activity impacts. Supervision is carried out through a monitoring team that records student attendance and discipline. Development evaluation is in the form of activity reports divided into short-term and long-term. Evaluation of success will be seen through the report card scores of students' extracurricular activities given each month. (2) Supporting factors include the availability of facilities and infrastructure, competent implementing staff, and effective coordination. Inhibiting factors include ineffective time management and teacher discipline, limited substitute staff, and administrative constraints such as outstanding student payments. Keywords: Management, Extracurricular Activities, Minister of Education, Culture, Research, and Technology Regulation No. 12 of 2024